(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2026)
This paper examines the precise moment at which legal majority begins under Argentine law following the enactment of the Civil and Commercial Code of the Nation (Law 26,994). The central thesis argues that, unlike the previous regime of the Civil Code, Article 25 of the new Code eliminated the exception that allowed majority to be acquired at the very beginning of one’s eighteenth birthday. Under the former system, Article 128 expressly provided that incapacity ceased “on the day” the required age was reached, thereby creating an exception to the general rules on time computation. With its repeal, the general rules contained in Article 6—requiring the computation of full days—regain full applicability. Accordingly, minority status extends until the end of the eighteenth birthday, and majority is attained at midnight at the start of the following day. The author challenges the prevailing scholarly position that continues to uphold the traditional interpretation despite the removal of its statutory basis. The paper further analyzes the practical implications of this hermeneutical shift, particularly regarding the validity and nullity of legal acts performed by individuals who have not yet completed their eighteenth year.